2021
DOI: 10.1002/ecy.3327
|View full text |Cite
|
Sign up to set email alerts
|

Unclusterable, underdispersed arrangement of insect‐pollinated plants in pollinator niche space

Abstract: Pollinators can mediate facilitative or competitive relationships between plant species, but the relative importance of these two conflicting phenomena in shaping community‐wide pollinator resource use remains unexplored. This article examines the idea that the arrangement of large samples of plant species in Hutchinsonian pollinator niche space (n‐dimensional hypervolume whose axes represent pollinator types) can help to evaluate the comparative importance of facilitation and competition as drivers of pollina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 96 publications
(128 reference statements)
1
12
0
Order By: Relevance
“…Second, pollinator sharing in this community may have resulted in reproductive benefits for plants (Bergamo et al 2020). By blooming together, plants may promote facilitation, which is a reproductive strategy that increases the number of visitors, even if they deposit heterospecific pollen (Tur et al 2016, Thomson et al 2019, Herrera 2021). Facilitation has been an important factor decreasing pollen limitation and determining functional patterns in other plant communities pollinated by hummingbirds (Wolowski et al 2017, Bergamo et al 2018), and our results suggest this relationship in the studied community.…”
Section: Discussionmentioning
confidence: 99%
“…Second, pollinator sharing in this community may have resulted in reproductive benefits for plants (Bergamo et al 2020). By blooming together, plants may promote facilitation, which is a reproductive strategy that increases the number of visitors, even if they deposit heterospecific pollen (Tur et al 2016, Thomson et al 2019, Herrera 2021). Facilitation has been an important factor decreasing pollen limitation and determining functional patterns in other plant communities pollinated by hummingbirds (Wolowski et al 2017, Bergamo et al 2018), and our results suggest this relationship in the studied community.…”
Section: Discussionmentioning
confidence: 99%
“…Although a rigorous demonstration of their pollinating effectiveness would have required controlled experiments, circumstantial evidence suggests that the Nitidulidae recorded in pollinator censuses in this study should be considered as true pollinators of most plant species where they occurred. Examination of ~300 close-up photographs of Nitidulidae taken as part of pollinator census work (Herrera 2020(Herrera , 2021 revealed that they often S1 for details). Plant clades marked by arcs match those in Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, and perhaps more importantly, this study has provided a case example for the application of an analytical procedure apt to dissect objectively the importance of phylogenetic legacies, gross floral traits and ecological scenarios as predictors of interspecific variation in pollinator composition. Applied to sufficiently large and phylogenetically diverse samples of animal-pollinated plants, the analytical tools used here can help to shed light, from a different angle, on extant controversial issues in pollination research beyond ad hoc interpretations usually applied to small species samples (e.g., the reality of so-called "pollination syndromes"; Herrera 2020Herrera , 2021Krakos & Austin 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on bee pollinator composition and air temperature at the foraging sites of different bee species were collected during January-December 1997-2022 in a relatively small area of the Sierra de Cazorla, Jaén Province, southeastern Spain (see Herrera 2021: Fig. 2, for map of sampling sites).…”
Section: Methodsmentioning
confidence: 99%